Etika Emosi dalam Praktik Keadilan Sosial: Pendekatan Filosofis terhadap Afeksi dan Aksi - Rona Utami; Siti Murtiningsih; Amelsia Lintang Ardanadi; Dela Khoirul Ainia (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
Social justice within the framework of Pancasila often stands in contrast to the realities of everyday life, which are marked by inequality, marginalization, and the erosion of human dignity. This tension raises a fundamental philosophical question: how can social justice be meaningfully enacted in a society fraught with emotional tensions and moral dilemmas? To date, studies on justice have largely focused on normative and structural aspects, while the role of emotion in shaping moral awareness and ethical action has received relatively little attention. This research seeks to understand how emotions—such as guilt, shame, anger, disappointment, and love—influence moral perception and responses to injustice. It employs a qualitative approach using a philosophical-interpretative method, combining philosophical literature reviews, emotion theory, and in-depth interviews with purposively selected communities. Data collection was conducted through literature studies and interviews, while analysis was carried out using thematic interpretation and philosophical reflection. The findings reveal that emotions play a crucial role in shaping ethical orientations toward justice. Guilt and shame act as catalysts for reflection and solidarity, while anger, disappointment, and love serve as moral energies that drive active engagement in the struggle for justice. These insights enrich the discourse of applied ethics by positioning emotion as a vital foundation in the formulation and implementation of social justice.